Composite wire rod and electrical property test probe
By adopting composite wires with specific structures and materials, the problems of insufficient conductivity, hardness and wear resistance in high-current tests of existing probes are solved, and efficient high-frequency and high-speed chip testing is achieved, extending the service life of the probe.
Patent Information
- Application Number
- CN202311107323.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-30
- Publication Date
- 2025-02-28
AI Technical Summary
Existing composite probes cannot meet the requirements of advanced chip testing at high currents, especially in terms of conductivity, hardness and wear resistance.
A composite wire material is used, which includes a core and a cover part. The cover part occupies more than 50% of the cross-sectional area, has an average body resistivity less than 12μΩ·cm, and the Vickers hardness of the core material is greater than 300Hv. By controlling the line diameter, coverage ratio and material characteristics, high conductivity, high hardness and high wear resistance are achieved.
Combining high conductivity, high hardness and high wear resistance, the composite wire produces probes that perform excellently in high-frequency and high-speed advanced chip tests, with a prolonged service life and are suitable for high-current applications.
Smart Images

Figure CN119541926A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a composite wire, and in particular to a composite wire suitable for preparing a probe for testing electronic components; in addition, the present invention also relates to an electrical testing probe made of the composite wire. Background Art
[0002] The semiconductor industry can be roughly divided into the stages of design, manufacturing, packaging and testing. When the cost of wafers is very high, testing is performed after wafer manufacturing and chip packaging. Whether defective chips can be detected and screened out from the production line in real time is very important for the control of overall production costs. A probe card is essentially a device that electrically connects multiple contact pads to corresponding channels of a test instrument. The test machine performs its functional tests, especially electrical function tests. Usually, the test head on the probe card includes a large number of contact components or contact probes, which must be made of fine alloy wires with good mechanical and electrical properties, and have at least one contact portion for the component under test to correspond to multiple contact pads. For example, the probe directly contacts the pads or bumps on the chip to bring out the chip signal, and then cooperates with peripheral test instruments and software to achieve the purpose of measurement.
[0003] Palladium (Pd) alloys are often used as probe materials for semiconductor wafer testing, post-packaging testing, or light-emitting diode chip testing due to their excellent electrical performance and reliability. However, the conductivity of palladium alloys is still lower than that of copper (Cu). When testing with higher currents, the current resistance of palladium alloy materials will show its disadvantages. Advanced and high-end probe card manufacturers use micro-electromechanical system (MEMS) technology to combine precious metals and non-precious metals to make composite probes in order to meet the testing requirements under high currents. However, existing composite probes still cannot meet various needs. Summary of the invention
[0004] In view of the defects faced by the prior art, the purpose of the present invention is to provide a composite wire that has good conductivity, high hardness and good wear resistance. Therefore, the probe made of the composite wire is particularly in line with the high-frequency, high-speed and high-order chip testing requirements.
[0005] Another object of the present invention is to provide a composite wire having good machinability.
[0006] To achieve the above-mentioned purpose, the present invention provides a composite wire, comprising: a core in a linear shape; and a coating; the coating surrounds the outer peripheral wall of the core. The wire diameter of the composite wire is less than 1 mm, the composite wire has a cross section; based on the overall area of the cross section, the area occupied by the coating is greater than 50%; the average volume resistivity of the composite wire is less than 12 μΩ·cm; the average volume resistivity of the material of the coating is less than 12 μΩ·cm; and the Vickers hardness of the material of the core is greater than 300 Hv.
[0007] The composite wire of the present invention controls the following technical features simultaneously: (I) the wire diameter of the composite wire is less than 1 mm, (II) the area occupied by the coating is greater than 50% based on the overall area of the cross section, (III) the average volume resistivity of the composite wire is less than 12 μΩ·cm, (IV) the average volume resistivity of the material of the coating is less than 12 μΩ·cm, and (V) the Vickers hardness of the material of the core is greater than 300 Hv. Therefore, the composite wire has high conductivity, high hardness and high wear resistance. The probe made of the composite wire can avoid being easily deformed or worn too quickly during use, thereby ensuring the service life of the probe. Moreover, the probe is more suitable for applications under high current due to its low contact resistance, for example, it can meet the requirements of high-frequency and high-speed high-end chip testing. In addition, by simultaneously controlling the wire diameter of the cross section of the composite wire and the area ratio of the coating in the cross section, the composite wire can have good machinability.
[0008] According to the present invention, the cross section of the composite wire is defined as a cross section perpendicular to the axial direction of the composite wire. Therefore, the cross section of the composite wire may be circular or non-circular (for example but not limited to elliptical), rectangular or square, but not limited thereto.
[0009] In some embodiments, the cross section may be circular or non-circular, and in the cross section of the composite wire, the core may also be circular or non-circular. Preferably, when the cross section or the core is non-circular, the ratio of the major axis to the minor axis of the non-circular may be greater than 1 and less than or equal to 5, but is not limited thereto. In these embodiments, the covering portion is annular and surrounds the outer peripheral wall of the core.
[0010] Further, when the core is circular or non-circular, the maximum line distance through the midpoint of the core is defined as the major diameter, and half of the major diameter is defined as the radius of the core. Preferably, the radius of the core may be greater than 2 μm. More preferably, the radius of the core may be 7.5 μm to 160 μm, but is not limited thereto. Even more preferably, the radius of the core may be 30 μm to 160 μm.
[0011] In other embodiments, the cross section may be square or rectangular, and in the cross section of the composite wire, the core may also be square or rectangular. Preferably, when the cross section or the core is rectangular, the ratio of the long side to the short side of the rectangle may be greater than 1 and less than or equal to 5, but is not limited thereto. In these embodiments, the covering portion is a rectangular frame and surrounds the outer peripheral wall of the core.
[0012] Further, when the core is square or rectangular, the outer periphery of the core has two sets of parallel opposite sides, the longer of the two sets of sides is called the long side, and half of the long side is defined as the half-long side of the core. Preferably, the half-long side of the core can be greater than 2μm. More preferably, the half-long side of the core can be 7.5μm to 160μm, but not limited thereto. Even more preferably, the half-long side of the core can be 30μm to 160μm.
[0013] According to the present invention, the area ratio of the covering portion to the cross section is commonly known as the covering ratio. Preferably, based on the overall area of the cross section, the area occupied by the covering portion can be 60% to 90%, but is not limited thereto. More preferably, based on the overall area of the cross section, the area occupied by the covering portion can be 77% to 90%.
[0014] According to the present invention, the wire diameter of the composite wire refers to the length of the longest axis of the cross section, that is, the diameter of a circle, the long axis of a non-circular shape, the side length of a square, and the long side of a rectangle. Preferably, the wire diameter of the composite wire is 30 micrometers (μm) to 600 μm, but not limited thereto. More preferably, the wire diameter of the composite wire is 30 μm to 60 μm.
[0015] According to the present invention, when the composite wire and the core are both circular or non-circular, the thickness of the coating is obtained by deducting the radius of the core from half of the wire diameter of the composite wire. In addition, when the composite wire and the core are both square or rectangular, the thickness of the coating is obtained by deducting half of the long side of the core from half of the wire diameter of the composite wire. In the cross section of the composite wire, preferably, the thickness of the coating is greater than 5μm, but is not limited thereto. More preferably, the thickness of the coating is 9μm to 165μm. Even more preferably, the thickness of the coating is 60μm to 165μm.
[0016] In some embodiments, the radius / half-long side of the core is equal to the thickness of the cladding. In other embodiments, the radius / half-long side of the core is less than the thickness of the cladding.
[0017] According to the present invention, the material of the core is not completely the same as the material of the coating. Preferably, the material of the core includes gold alloy, silver alloy, palladium metal, palladium alloy, copper metal, copper alloy or stainless steel, but is not limited thereto. Specifically, the gold (gold, Au) alloy means that the gold metal accounts for more than 50 weight percent (wt%) of the total weight of the gold alloy; preferably, the gold alloy, in addition to gold, may also include aluminum (Aluminum, Al), copper, silver (Silver, Ag), magnesium (Magnesium, Mg), zinc (Zinc, Zn), ruthenium (Ruthenium, Ru), cobalt (Cobalt, Co), gallium (Gallium, Ga) or a combination thereof. The silver alloy means that the silver metal accounts for more than 50wt% of the total weight of the silver alloy; preferably, the silver alloy, in addition to silver, may also include copper, nickel (Nickel, Ni), zirconium (Zr), chromium (Chromium, Cr), aluminum, palladium or a combination thereof. The palladium alloy refers to a palladium metal that accounts for more than 30wt% of the total weight of the palladium alloy; preferably, the palladium alloy may contain copper, silver, platinum (Platinum, Pt), gold, iridium (Ir) or a combination thereof in addition to palladium. The copper alloy refers to a copper metal that accounts for more than 50wt% of the total weight of the copper alloy; preferably, the copper alloy may contain tin (Tin, Sn), phosphorus (Phosphorus, P), iron (Iron, Fe), nickel, zinc, beryllium (Beryllium, Be), titanium (Titanium, Ti), gold, silver, palladium or a combination thereof in addition to copper. More preferably, in the copper alloy, copper accounts for more than 90wt% of the total weight of the copper alloy. In addition, the stainless steel is a chromium-iron alloy; preferably, based on the total weight of the stainless steel, the chromium content is 15wt% to 30wt%, the iron content is 40wt% to 70wt%, and the carbon content is less than 0.2wt%. In addition, the stainless steel may contain nickel, molybdenum (Mo), vanadium (V), titanium, niobium (Nb), manganese (Mn), tungsten (W), aluminum, copper, carbon (C), phosphorus, sulfur (S), silicon (Si), nitrogen (N) or a combination thereof, in addition to chromium and iron, but is not limited thereto. The stainless steel may be austenite or γ-Fe, ferrite or α-Fe, or martensite.
[0018] According to the requirements for material properties in different terminal product applications, preferably, the material of the coating portion includes stainless steel, palladium alloy, nickel alloy, copper alloy or aluminum alloy, but is not limited thereto. The stainless steel can refer to the description of the stainless steel in the material of the core mentioned above. The palladium alloy can refer to the description of the palladium alloy in the material of the core mentioned above. The nickel alloy means that the nickel metal accounts for more than 50wt% of the total weight of the nickel alloy; preferably, the nickel alloy can also contain cobalt, chromium, iron, copper, silicon, carbon, manganese, titanium, tungsten, tantalum (Tantalum, Ta), phosphorus or a combination thereof in addition to nickel. The copper alloy can refer to the description of the copper alloy in the material of the core mentioned above. The aluminum alloy means that the aluminum metal accounts for more than 50wt% of the total weight of the aluminum alloy; preferably, the aluminum alloy can also contain silicon, iron, copper, manganese, magnesium, chromium, zinc, vanadium, titanium, zirconium or a combination thereof in addition to aluminum. More preferably, in the aluminum alloy, aluminum accounts for more than 90wt% of the total weight of the aluminum alloy.
[0019] Preferably, the Vickers hardness of the material of the core may be greater than 400 Hv, but not limited thereto. More preferably, the Vickers hardness of the material of the core may be greater than 535 Hv, but not limited thereto.
[0020] Preferably, the average volume resistivity of the material of the coating portion may be less than 4 μΩ·cm, but not limited thereto. More preferably, the average volume resistivity of the material of the coating portion may be less than 2.5 μΩ·cm, but not limited thereto.
[0021] Preferably, the average volume resistivity of the composite wire may be 1 μΩ·cm to 4 μΩ·cm or less than 4 μΩ·cm, but is not limited thereto. For example, the average volume resistivity of the composite wire may be 1.9 μΩ·cm to 3 μΩ·cm. More preferably, the average volume resistivity of the composite wire is less than 2.5 μΩ·cm, but is not limited thereto.
[0022] In some embodiments, if it is desired to further prevent the coating from being oxidized, the composite wire may include a protective layer formed on the outer surface of the coating, that is, the coating is sandwiched between the protective layer and the core. Preferably, the material of the protective layer may include gold metal, palladium metal or silver metal, but is not limited thereto; the protective layer may be formed by an electroplating process or a spraying process. Preferably, in the cross section of the composite wire, the thickness of the protective layer may be 0.1 μm to 4 μm, but is not limited thereto.
[0023] The composite wire of the present invention can be made by some common production methods, but it is not limited to the process exemplified in this specification. For example, the above production method can be a composite extrusion method (also known as a hot extrusion method; it mainly relies on the friction of the extrusion wheel to extrude and coat the unmelted or semi-melted coating material on the surface of the unmelted core), a casting and drawing composite method (it mainly casts the coating in a molten metal state on the surface of the core), a core filling continuous casting composite method (it mainly casts the core material and the coating material in a molten state first and then cools and joins them), a continuous extrusion and coating composite method (it mainly extrude and then join the semi-molten coating material and the core material), a drawing forming method (it mainly assembles the coating material and the core material first and then stretches them by mechanical force), a thin plate coating core material method (it mainly covers the coating on the surface of the core by welding, etc.), electroforming (electrodeposition on the core material), etc., but it is not limited to these.
[0024] In some embodiments, the aforementioned production method may include a heat treatment step to further adjust the material properties of the composite wire, but is not limited thereto.
[0025] The present invention further provides an electrical testing probe, which is made by subjecting the aforementioned composite wire to a surface insulation treatment process.
[0026] Preferably, the electrical test probe may be in the form of a spring probe, a snake probe, a cantilever probe, a contact probe, a wire probe, a MEMS probe, etc., but is not limited thereto.
[0027] Preferably, when the length of the electrical test probe is 19 mm, the contact resistance between the electrical test probe and the pad or bump may be 30 milliohms (mΩ) to 80 mΩ, but is not limited thereto.
[0028] In this specification, the wire diameter of the composite wire, the radius / half-long side of the core, the thickness of the coating, the thickness of the protective layer, etc. are all directly measured using a tool microscope. In addition, the average volume resistivity of the composite wire and the average volume resistivity of the material of the coating are calculated based on the resistance of the wire with a length of 30 cm under each wire diameter, and the volume resistivity formula; wherein, volume resistivity = (resistance / measured length) × wire cross-sectional area. The Vickers hardness of the core material is measured under the conditions of a load of 30 grams (g) and a load time of 10 seconds.
[0029] In this specification, the range represented by "a small value to a large value" means that the range is greater than or equal to the small value and less than or equal to the large value unless otherwise specified. For example, if the radius of the core is 7.5 μm to 160 μm, it means that the radius range of the core is "greater than or equal to 7.5 μm and less than or equal to 160 μm". BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a three-dimensional schematic diagram of an embodiment of the composite wire of the present invention.
[0031] Figure 2 yes Figure 1 Schematic diagram of the cross section of the composite wire.
[0032] Figure 3 FIG. 4 is a schematic cross-sectional view of another embodiment of the composite wire of the present invention.
[0033] Figure 4 4 is a schematic cross-sectional view of another embodiment of the composite wire of the present invention.
[0034] Figure 5 This is a schematic diagram of the contact resistance analysis of Analysis 4. DETAILED DESCRIPTION
[0035] Below, in order to verify the raw material properties of the core and the coating of the composite wire, the wire diameter of the composite wire and the coating ratio of the coating in the cross section on the composite wire, several composite wires are listed as examples below to explain the embodiments of the present invention in detail, and several comparative examples are provided as a comparison. Those skilled in the art can easily understand the advantages and effects that can be achieved by the present invention through the contents of this specification. It should be understood that the embodiments listed in this specification are only used to illustrate the embodiments of the present invention, and are not used to limit the scope of the present invention. Those skilled in the art can make various modifications and changes based on their common knowledge without departing from the spirit of the present invention to implement or apply the contents of the present invention.
[0036] Examples 1 to 13: Composite wire
[0037] Ingredients
[0038] 1. Stainless steel S: contains about 18wt% to 20.0wt% chromium, about 8.0wt% to 12.0wt% nickel, about 2wt% manganese, about 0.08wt% carbon, about 0.045wt% phosphorus, about 0.03wt% sulfur, about 1.0wt% silicon, and the rest is iron.
[0039] 2. Palladium alloy A: contains about 35.0 wt % to 45.0 wt % of palladium, about 30.0 wt % to 40.0 wt % of silver, and about 20.0 wt % to 30.0 wt % of copper.
[0040] 3. Palladium alloy B: contains about 45.0 wt % to 60.0 wt % of palladium, about 5.0 wt % to 15.0 wt % of silver, and about 35.0 wt % to 45.0 wt % of copper.
[0041] 4. Copper alloy I: contains greater than or equal to 99.5 wt % of copper and about 0.015 wt % to 0.04 wt % of phosphorus.
[0042] 5. Aluminum alloy I: contains greater than or equal to 98wt% palladium, about 0.15wt% iron, about 0.20wt% copper, about 0.05wt% manganese, about 0.45wt% to 0.90wt% magnesium, and about 0.20wt% to 0.60wt% silicon.
[0043] First, according to the type of material of the core and its Vickers hardness, the type of material of the coating and its average volume resistivity shown in Table 1, the composite wires of Examples 1 to 13 were prepared by a general method for manufacturing a composite wire; wherein each composite wire has an average volume resistivity as shown in Table 1, and each composite wire has a wire diameter as shown in Table 1; in the composite wire of each embodiment, in the cross section of the composite wire, the core has a radius as shown in Table 1, and the coating has a thickness and an area ratio (i.e., a coating ratio) as shown in Table 1.
[0044] For example, see Figure 1 , Figure 2 As shown, a composite wire 10 (such as Examples 1 to 13) of an embodiment of the present invention includes a linear core 12 and a coating 11 surrounding the outer peripheral wall of the core 12. The composite wire 10 has a cross-section S, and the cross-section S of the composite wire 10 is defined as a cross-section perpendicular to the axial direction of the composite wire 10; the cross-section S is circular, and the cross-section S has a wire diameter D of less than 1 mm (i.e., the maximum outer diameter passing through the midpoint of the cross-section S). In the cross-section S of the composite wire 10, the core 12 is also circular and the radius r1 of the core 12 is greater than 10 μm, while the coating 11 is annular, and the thickness H1 of the coating 11 is greater than 10 μm. Based on the overall area of the cross-section S, the area occupied by the coating 11 is greater than 50%. From Figure 2 It can be seen that the wire diameter D of the composite wire 10 is equivalent to twice the total length of the thickness H1 of the coating 11 and the radius r1 of the core 12, that is, D=2×(H1+r1).
[0045] See also Figure 3As shown, a composite wire 10 according to another embodiment of the present invention includes, from the inside to the outside, a linear core 12, a cladding 11 surrounding the outer peripheral wall of the core 12, and a protective layer 13 surrounding the outer surface of the cladding 11. In the cross section S of the composite wire 10, the core 12 is circular and the radius r1 of the core 12 is approximately 40 μm, while the cladding 11 and the protective layer 13 are both annular; wherein the thickness H1 of the cladding 11 is approximately 45 μm, and the thickness H2 of the protective layer 13 is approximately 0.5 μm to 2 μm. Based on the overall area of the cross section S, the area occupied by the cladding 11 is greater than 50%. From Figure 3 It can be seen that the wire diameter D of the composite wire 10 is equivalent to twice the total length of the thickness H2 of the protective layer 13, the thickness H1 of the coating 11, and the radius r1 of the core 12, that is, D=2×(H2+H1+r1).
[0046] See also Figure 4 As shown, a composite wire 10 according to another embodiment of the present invention comprises a linear core 12 and a coating 11 surrounding the outer peripheral wall of the core 12. The composite wire 10 has a cross section S, the cross section S is square, the core 12 in the cross section S is also square, and the coating 11 is a rectangular frame. In the cross section S of the composite wire 10, the cross section S has a wire diameter D (i.e., the side length of the aforementioned square) less than 1 mm, the half side length r2 of the core 12 is greater than 10 μm, and the thickness H1 of the coating 11 is greater than 10 μm; based on the overall area of the cross section S, the area occupied by the coating 11 is greater than 50%. From Figure 4 It can be seen that the wire diameter D of the composite wire 10 is equivalent to twice the sum of the thickness H1 of the coating 11 and the half length r2 of the core 12, that is, D=2×(H1+r2).
[0047] Comparative Examples 1 to 2: Palladium Alloy Wire
[0048] Comparative Example 1 is a wire made of palladium alloy A, with a wire diameter of 500 mm, an average volume resistivity of 11 μΩ·cm, and a Vickers hardness of 438 Hv. The wire of Comparative Example 2 has the same wire diameter as Comparative Example 1, but is made of palladium alloy B, with an average volume resistivity of 6.5 μΩ·cm and a Vickers hardness of 398 Hv.
[0049] Comparative Examples 3 to 5: Stainless Steel Wire
[0050] The wires of Comparative Examples 3 to 5 are all made of stainless steel S, and their wire diameters, Vickers hardnesses, and average volume resistivities are shown in Table 1.
[0051] Test Example 1: Vickers Hardness Analysis
[0052] In this test example, the composite wires of Examples 1 to 13, the palladium alloy wires of Comparative Examples 1 to 2, and the stainless steel wires of Comparative Examples 3 to 5 were respectively taken with a length of 1 cm, and were first embedded with epoxy resin and hardener; then, an automatic grinder (manufacturer: Struers; model: Tegramin-25) was used to grind the wires in order with silicon carbide sandpaper of #80, #240, #400, #800, #1000, #1500, #2000, and #3000. The samples were ground and then polished to a mirror surface with 1.0 μm and 0.03 μm alumina powder solutions to obtain cross-sectional samples of the embodiments and comparative examples. The samples were sequentially tested for Vickers hardness of the core of each sample using a Vickers hardness tester (manufacturer: Mitutoyo Instrument Co., Ltd., model: 810-353DC) with a load of 30 g and a load time of 10 seconds. The measurements were repeated for 5 points and the average results were recorded in Table 1.
[0053] Test Example 2: Average Volume Resistivity Analysis
[0054] In this test example, the coating materials of the composite wires of Examples 1 to 13 with a length of 30 cm were taken as samples, and the resistance of each sample was measured in sequence by a microresistance meter (manufacturer: HIOKI, model: RM-3544); the resistance measurement was repeated 3 times and the average value was taken, and the volume resistivity formula was used to calculate the result, and the results were recorded in Table 1.
[0055] Volume resistivity = (resistance / measurement length) × wire cross-sectional area.
[0056] In addition, the composite wires of Examples 1 to 13, the palladium alloy wires of Comparative Examples 1 to 2, and the stainless steel wires of Comparative Examples 3 to 5 with a length of 30 cm were taken as samples to be tested, and the average volume resistivity of the composite wires of Examples 1 to 13, the average volume resistivity of the palladium alloy wires of Comparative Examples 1 to 2, and the average volume resistivity of the stainless steel wires of Comparative Examples 3 to 5 were obtained using the same analysis method as above, and the results are recorded in Table 1.
[0057] Test Example 3: Morphological Analysis of Wire Cross Section
[0058] In this test example, a sample with a length of 1 cm was embedded with epoxy resin and hardener, and then ground with silicon carbide sandpaper of #80, #240, #400, #800, #1000, #1500, #2000, and #3000 in sequence using an automatic grinder (manufacturer: Struers; model: Tegramin-25). Then, each sample was polished to a mirror surface with a 1.0 μm and 0.03 μm alumina powder solution, thereby obtaining samples of the cross sections of the composite wires of Examples 1 to 13, the palladium alloy wires of Comparative Examples 1 to 2, and the stainless steel wires of Comparative Examples 3 to 5. Next, each set of samples was observed with a tool microscope (manufacturer: Lixun Technology Co., Ltd., model: M21G+OP) to obtain the radius of the core, the thickness of the coating, the wire diameter of the composite wire, the area ratio of the coating in the cross section, and the area ratio of the core in the cross section of each set of samples; wherein, 3 samples were measured for each set of embodiments and comparative examples, and the above average results were recorded in Table 1.
[0059] Table 1
[0060]
[0061]
[0062] Analysis 4: Contact resistance analysis
[0063] Please refer to Figure 5 In this test example, the composite wires of Examples 7, 9, 10, and 11, the palladium alloy wire of Comparative Example 1, and the stainless steel wire of Comparative Example 3 with a length of 19 mm are taken as representatives, and the aforementioned wires are respectively ground into test needles T, so that each test needle T is in contact with a copper column P (8 mm in diameter, 3 cm in length, 99.999% pure copper, and its surface is polished to a mirror surface), and then a microresistance meter RM (manufacturer: HIOKI Electric Co., Ltd., model: RM-3544) is used to clamp the test needles T separately. One end of the needle T and one end of the copper pillar P are then measured to obtain a "test resistance value"; in fact, the "test resistance value" is the sum of the resistance value of the test needle T, the contact resistance value between the test needle T and the copper pillar P, and the resistance value of the copper pillar P; however, since the resistance value of the test needle T and the resistance value of the copper pillar P are more than two orders of magnitude smaller than the "contact resistance value between the test needle T and the copper pillar P", the "test resistance value" measured by the microresistance meter RM directly represents the "contact resistance value between the test needle T and the copper pillar P". The test needle T of each group of embodiments and comparative examples is measured 3 times, and the average result is recorded in Table 2.
[0064] Analysis 5: Breaking Limit (BL) analysis
[0065] In this test example, the composite wires of Examples 7, 9, 10, and 11, the palladium alloy wire of Comparative Example 1, and the stainless steel wire of Comparative Example 3 are represented, and each of the aforementioned wires with a length of 10 mm is taken as a sample. Then, each sample is subjected to a tensile tester (manufacturer: Yang Yi Technology Co., Ltd., model: QC-H35A2-S01), and the load value at the breaking point of each sample is recorded as the tensile breaking load. After each group repeats the test 3 times, the obtained values are averaged and the results are recorded in Table 2. Among them, the test conditions are as follows: the stretching speed is 10 mm / minute, and the upper limit of measurement is 10 kilograms of force (kgf). If the sample continues to be stretched to the upper limit of the load of 10 kgf and still does not break, it is recorded as >10 kgf.
[0066] Analysis 6: Yield load analysis
[0067] From the tensile test of the above analysis 5, the load-elongation curve of each sample is obtained, and the yield load is defined by the 0.2% intercept yield load method on the load-elongation curve of each sample, that is, a straight line parallel to the elastic deformation area line is drawn from the position of 0.2% elongation on the elongation axis, and the above straight line intersects the load-elongation curve at a point, and the load at this point is the yield load. The samples of each group of embodiments and comparative examples were tested 3 times, and the obtained values were averaged, and the results were recorded in Table 2.
[0068] Analysis 7: Young's coefficient analysis
[0069] In the tensile test of the above analysis 5, the Young's modulus of each sample was obtained from the slope of the linear area in the elastic deformation area on the strain-stress curve of each sample. The test was repeated 3 times for each group of examples and comparative examples, and the obtained values were averaged and the results were recorded in Table 2.
[0070] Table 2
[0071] Group Contact resistance (mΩ) BL(kgf) Falling load (gf) Young's modulus (GPa) Example 7 95.7 >10 7412 56.6 Example 9 40.3 >10 7268 54.5 Example 10 40.16 >10 5619 49.7 Embodiment 11 38.2 >10 5880 48.3 Comparative Example 1 48.66 >10 >10000 55.1 Comparative Example 3 385.4 >10 6594 85.1
[0072] Discussion of experimental results
[0073] According to the results in Table 1, it can be seen from the comparison between the composite wires of Examples 1 to 7 and the stainless steel wire of Comparative Example 3 that the composite wires of Examples 1 to 7 and the stainless steel wire of Comparative Example 3 all have high hardness; furthermore, the composite wires of Examples 1 to 7 are able to significantly reduce the average volume resistivity of the stainless steel wire to 2.0 μΩ·cm to 2.2 μΩ·cm by having the coating portion having a "coating ratio greater than 50%" (e.g., 77.01% to 80.15%), compared with the average volume resistivity of the stainless steel wire of Comparative Example 3 (82.8 μΩ·cm), the average volume resistivity decreases by more than 97%, which proves that the composite wire of the present invention can indeed have better conductivity while maintaining high hardness.
[0074] Similarly, it can be seen from the comparison between the composite wires of Examples 8 to 11 and the palladium alloy wire of Comparative Example 1 that the core of the composite wire can also maintain a hardness equivalent to that of the palladium alloy wire, so it can meet the application specifications of the test probe. Furthermore, the composite wires of Examples 8 to 11 can significantly reduce the average volume resistivity of the palladium alloy wire to 1.9 μΩ·cm to 3.0 μΩ·cm by having the coating portion with a "coating ratio greater than 50%" (e.g., 60.81% to 88.12%). Compared with the average volume resistivity of the palladium alloy wire of Comparative Example 1 (11 μΩ·cm), the average volume resistivity can be reduced by more than 72%, which proves that the composite wire of the present invention does have better conductivity.
[0075] In addition, it can be seen from the comparison between the composite wires of Examples 12 to 13 and the palladium alloy wire of Comparative Example 2 that the core of the composite wire can also maintain a hardness equivalent to that of the palladium alloy wire, so it can meet the test probe application specifications. Furthermore, the composite wires of Examples 12 to 13 can significantly reduce the average volume resistivity of the palladium alloy wire to 2.6 μΩ·cm to 2.9 μΩ·cm by having the coating portion with a "coating ratio greater than 50%" (for example, 77.56% to 79.34%). Compared with the average volume resistivity of Comparative Example 2 (6.5 μΩ·cm), the average volume resistivity can be reduced by more than 55%, which proves that the composite wire of the present invention does have better conductivity.
[0076] According to the results in Table 2, it can be seen from the comparison between the composite wires of Examples 9 to 11 and the palladium alloy wire of Comparative Example 1 that even if the core of the composite wires of Examples 9 to 11 and the palladium alloy wire of Comparative Example 1 use the same palladium alloy composition and have similar wire diameters, the composite wires of Examples 9 to 11 can have a smaller average volume resistivity at a coating ratio of 60.81% to 88.12%, and maintain their contact resistance and machinability (e.g., tensile fracture load, yield load, and Young's modulus). Similarly, it can be seen from the comparison between the composite wire of Example 7 and the stainless steel wire of Comparative Example 3 that even if the core of the composite wire of Example 7 and Comparative Example 3 use the same stainless steel and have similar wire diameters, the composite wire of Example 7 obviously has a smaller average volume resistivity and contact resistance, and maintains its machinability (e.g., tensile fracture load, yield load, and Young's modulus). It can be proved that the composite wire of the present invention can indeed have better conductivity, wear resistance, and machinability.
[0077] In summary, the present invention appropriately controls the wire diameter range of the composite wire, the coating ratio of the coating, the average volume resistivity range of the composite wire and the coating, and the Vickers hardness range of the core material, so that the composite wire of the present invention has high conductivity, high hardness and high wear resistance. The probe made of the composite wire can avoid being easily deformed or worn too quickly during use, thereby ensuring the service life of the aforementioned probe, and is particularly suitable for high-end chip testing requirements under high current.
[0078] The above embodiments are merely examples for the convenience of description. The scope of rights claimed by the present invention should be based on the claims, but not limited to the above embodiments.
Claims
1. A composite wire comprising: a core in the form of a line; and a covering portion, the covering portion surrounding the outer peripheral wall of the core; in, The wire diameter of the composite wire is less than 1 mm; The composite wire has a cross section; based on the overall area of the cross section, the area occupied by the covering portion is greater than 50%; The average volume resistivity of the composite wire is less than 12 micro-ohm·cm; The average volume resistivity of the material of the coating is less than 12 micro-ohms·cm; The Vickers hardness of the material of the core is greater than 300 Hv.
2. The composite wire according to claim 1, wherein The average volume resistivity of the composite wire is less than 4 micro-ohm·cm; the average volume resistivity of the material of the coating portion is less than 4 micro-ohm·cm.
3. The composite wire according to claim 1, wherein The wire diameter of the composite wire is 30 microns to 600 microns.
4. The composite wire according to claim 1, wherein Based on the overall area of the cross section, the area occupied by the covering portion is 60% to 90%.
5. The composite wire according to claim 4, wherein: Based on the overall area of the cross section, the area occupied by the covering portion is 77% to 90%.
6. The composite wire according to claim 1, wherein In the cross section of the composite wire, the cross section is circular or non-circular, and the core is circular or non-circular; wherein the radius of the core is 30 micrometers to 160 micrometers.
7. The composite wire according to claim 1, wherein In the cross section of the composite wire, the cross section is circular or non-circular, the core is circular or non-circular, the cladding is annular, and the thickness of the cladding is 9 micrometers to 165 micrometers.
8. The composite wire according to claim 7, wherein: In the cross section of the composite wire, the coating portion has a thickness of 60 μm to 165 μm.
9. The composite wire according to claim 1, wherein The Vickers hardness of the material of the core is greater than 535 Hv.
10. The composite wire according to any one of claims 1 to 9, wherein The material of the core includes gold alloy, silver alloy, palladium metal, palladium alloy, copper metal, copper alloy or stainless steel.
11. The composite wire according to any one of claims 1 to 9, wherein The material of the covering portion includes stainless steel, palladium alloy, nickel alloy, copper alloy or aluminum alloy.
12. The composite wire according to any one of claims 1 to 9, wherein The composite wire further comprises a protective layer, which is formed on the outer surface of the covering portion; wherein the material of the protective layer comprises gold metal, palladium metal or silver metal.
13. An electrical testing probe, which is made by subjecting the composite wire according to any one of claims 1 to 12 to a surface insulation treatment process.